2012 IEEE International Energy Conference and Exhibition (ENERGYCON) 2012
DOI: 10.1109/energycon.2012.6348293
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility analysis of second life applications for Li-Ion cells used in electric powertrain using environmental indicators

Abstract: The recently increase of the EV/PHEV market is in part due to the technological progress of battery systems. The energy storage and charging are the critical aspects of an electric vehicle; Li-Ion batteries allow an increase in storage performance and efficiencies despite the needs of a high number of cells. The single Li-Ion cell is constituted by metals, graphite, various salts and electrolytes which result difficult to dispose of or recycle. Therefore the expected environmental sustainability of any EV is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 7 publications
(7 reference statements)
0
48
0
6
Order By: Relevance
“…These results do not seem bad when regarding the number of cycles these batteries can do in comparison to the 1000 cycles reported by Ciccioni et al [24], the 1500 cycles on ancillary services from Strickland et al [25], or between 2000 and 1000 full equivalent cycles reported by Muenzel et al [26] on batteries working in the range from 40% to 100% DoD, but they are alarming in terms of days. If batteries should work continuously under exposed load conditions, they will certainly not enter into the market.…”
Section: Discussionmentioning
confidence: 61%
“…These results do not seem bad when regarding the number of cycles these batteries can do in comparison to the 1000 cycles reported by Ciccioni et al [24], the 1500 cycles on ancillary services from Strickland et al [25], or between 2000 and 1000 full equivalent cycles reported by Muenzel et al [26] on batteries working in the range from 40% to 100% DoD, but they are alarming in terms of days. If batteries should work continuously under exposed load conditions, they will certainly not enter into the market.…”
Section: Discussionmentioning
confidence: 61%
“…Rather, the focus is on market participation of conventional generators [17], renewable generators [18], and loads [19], [20]. Finally, this paper is also related to the recent studies on reusing secondlife batteries, e.g., see [21], [22]. However, those studies do not discuss optimal bidding and bulk energy market participation.…”
Section: B Comparison With Related Workmentioning
confidence: 99%
“…More specifically, the real-time market prices are higher when the day-ahead market prices are higher. Given the statistical dependency between the dayahead and the real-time market prices in practice, it is better to use the more realistic solution in (22), see Section IV.…”
Section: A Solving the Inner Subproblemmentioning
confidence: 99%
“…The electric companies are paying special attention to the developments on storage systems providing energy services, such as "area regulation", "transmission and distribution deferral" and "power quality" among others (D. Rastler 2010), (Cready et al 2003), (Ciccioni et al 2012). However, these applications require high power and energy systems that imply the incorporation of hundreds of EV batteries (Heymans et al 2014) that are still not yet available.…”
Section: Methodsmentioning
confidence: 99%